Phytochemical, Antioxidant and Antibacterial Screening of Orthosiphon stamineus Leaf Extract Two Phenotypes - Waras Nurcholis; Fachrur Rizal Mahendra; Milanda Fiorella Gultom; Safira Khoirunnisa; Mayang Anggita Cahya Kurnia; Hamdan Hafizh Harahap (Jurnal Jamu Indonesia, 2022)
Kumis kucing (Orthosiphon stamineus) is a medicinal plant that can treat various diseases. Kumis kucing has been known to contain bioactive compounds, namely polyphenol, alkaloid, and terpenoid which have antioxidant, antibacterial, antiviral, anti-inflammatory, anti-allergic and anti-cancer activities. This study aims to determine the phytochemical content, antioxidant activity, and antibacterial activity of the cat's whiskers leaf extract. Kumis Kucing leaf extract was obtained by sonication-maceration method. Antioxidant activity test of cat's kumis leaf extract was tested using the CUPRAC and ABTS methods. The results showed that the kumis kucing’s leaf extract contains bioactive compounds of polyphenol, alkaloid, and terpenoid. The highest average antioxidant activity was produced by the purple phenotype cat whiskers leaf extract using the ABTS method, which was 168.68 µg TE/g dry weight. The highest average antibacterial activity in Escherichia coli  strain was obtained from leaf extract of purple phenotype cat whiskers (U2) with an inhibition zone diameter of 3.2 mm.